Isu Document Fraud dalam Fenomena Pencari Suaka: Studi Kasus Imigran Indonesia di Amerika Serikat - Christian Silitonga; Hermini Susiatiningsih; Satwika Paramasatya (Journal of International Relations Diponegoro, 2018)
The flows of Indonesian immigrants in United States experienced significant growth,especially in the 1980s until the beginning of the 21st century. Starting from the 2000sthere was a growing trend among Indonesian immigrants to obtain United Statespermanent resident status through seeking asylum. This study will explain the crime in theform of document fraud committed by Indonesian immigrants in the United States in orderof obtaining asylum. This study uses the transnational crime theory to explain analyze theeffort of Indonesian immigrants who uses document fraud during process of gettingasylum as a form of transnational crime. The data collected in this study varied rangingfrom primary sources which obtained through interviews, and from secondary sourceswhich obtained from literature reviews, official government documents, and media inwhich were then analyzed through content analysis. The results of this study indicate thatmajority of Indonesian immigrants who seek asylum from the United States uses documentfraud during the process of applying the status.